2003
DOI: 10.1016/j.jhevol.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain expansion and comparative prenatal ontogeny of the non-hominoid primate cranial base

Abstract: The basicranium is the keystone of the primate skull, and understanding its morphological interdependence on surrounding soft-tissue structures, such as the brain, can reveal important mechanisms of skull development and evolution. In particular, several extensive investigations have shown that, across extant adult primates, the degree of basicranial flexion and petrous orientation are closely linked to increases in brain size relative to cranial base length. The aim of this study was to determine if an equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
43
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 54 publications
12
43
3
2
Order By: Relevance
“…The age variable EGA was computed from biparietal diameter and is therefore susceptible to added variances such as head shrinkage and deformation. However, this and previous studies Spoor, 2002, 2004;Jeffery, 2003) have shown that the informative and comparative value of this computed age variable far outweighs any possible deleterious effects of the added noise. Head position is another possible source of unaccounted variance since it may have directly affected laryngeal position and thereby indirectly influenced pharyngeal dimensions in a number of specimens.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…The age variable EGA was computed from biparietal diameter and is therefore susceptible to added variances such as head shrinkage and deformation. However, this and previous studies Spoor, 2002, 2004;Jeffery, 2003) have shown that the informative and comparative value of this computed age variable far outweighs any possible deleterious effects of the added noise. Head position is another possible source of unaccounted variance since it may have directly affected laryngeal position and thereby indirectly influenced pharyngeal dimensions in a number of specimens.…”
Section: Discussionsupporting
confidence: 41%
“…Although the value of the coefficient is low, it remained statistically significant while controlling for background growth-related variances. These findings may explain the continued discrepancy between adult interspecific data that point to increases in relative brain size as the major influence on cranial base angulation and fetal data that do not [compare Ross and Ravosa (1993), Spoor (1997), and Ross et al (2004) to Jeffery and Spoor (2002) and Jeffery (2003)]. It is plausible that the fetal data reflect a different mechanism of basicranial angulation (i.e., retroflexion due to oropharyngeal enlargement) that may also be present across genera but is masked by the more prevailing influence of brain expansion (Jeffery, 2003).…”
Section: Table 2 Landmarks and Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…Note that Alouatta seniculus, an arboreal quadrupedal taxon that can maintain more orthograde body postures during bouts of locomotion (i.e., climbing, walking, and bridging) (Fleagle and Mittermeier, 1980;Youlatos, 1993Youlatos, , 1998, exhibits a very large angle value and often groups with Lemur catta and Varecia variegata, both dedicated terrestrial/arboreal quadrupeds (Rowe, 1996;Fleagle, 1999). Such a value indicates pronograde head and neck postures (Strait and Ross, 1999), probably related to this species' enlarged hyolaryngeal complex (Biegert 1963;Jeffery, 2003). …”
mentioning
confidence: 99%
“…• Jeffery 33 , in a comparative study of intrauterine skull base growth in nonhuman primates, questions the spatial-packing hypothesis.…”
Section: Mccarthymentioning
confidence: 99%